EMPOWERING WOMEN THROUGH IMPLEMENTING HORIZONTAL NET INNOVATION FOR SEAWEED CULTIVATION IN NORTH BUTON REGENCY - Maruf Kasim; La Baco Sudia; Nurdiana Nurdiana; Wardha Jalil (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
Seaweed cultivation is an important activity in most coastal villages in Indonesia. Most of the seaweed cultivation activities are carried out by men. This is because the longline cultivation method requires a lot of effort. Women only help in small processes such as tying and drying. One of the severe problems disturbing seaweed cultivators is the existence of fish pests that attack seaweed. This community service activity aims to implement seaweed cultivation innovations to increase seaweed production as well as the role of women in cultivation. Horizontal net innovation can prevent seaweed from being attacked by fish pests in seaweed cultivation. This community service activity was carried out in one of the coastal villages in Kulisusu District in North Buton Regency. This service activity is carried out through training and operational assistance using the horizontal net tool. As a result of the implementation of the activity, it was found that the community, especially women, was very enthusiastic about participating in the training. This activity was attended by 20 women consisting of representatives of seaweed cultivators around the waters of the Ereke sub- district. Output This activity is to provide increased knowledge and skills in operating the horizontal net, especially in empowering the role of women. It is easier for female seaweed cultivators to catch material and can immediately implement horizontal nets. The operation of this horizontal net tool is easy because the method used is very simple and does not require a lot of energy to operate. The increase in seaweed production is not determined by who the actor is cultivating but by using good and correct methods.